Regional transport of aerosols from northern India and its impact on boundary layer height and air quality over Chennai, a coastal megacity in southern India - S. Ali; S. Ali; C. Sarangi; S. K. Mehta (Atmospheric Chemistry and Physics)
Anticyclonic wind circulation is prevalent over India during the winter season, causing advection of air masses from northern India towards southeastern coastal Indian and the adjoining Bay of Bengal (BoB) regions. In this study, we use a synergy of satellite, radiosonde, and ground-based measurements to characterize the phenomenon of regional transport episodes (RTEs) and their impact on the boundary layer height and air quality over Chennai, a tropical South Asian megacity. The long-term satellite data and back-trajectory analysis enable us to detect the occurrence of RTE over Chennai, which persists for a duration of 2–4 d. The transported aerosol is generally located at altitudes of ∼ 1–3 km along the eastern coast of India. The duration of these RTEs in the winter season over Chennai accounts for ∼ 10 %–15 % of the days, which demonstrates an increasing trend over the last decade. Radiosonde analysis over the five sites located en route to the transport pathway illustrates distinct aerosol-associated warming (1–1.5 K) at altitudes corresponding to these elevated layers and hence a strong enhancement in lower-tropospheric stability during the RTE. In agreement, the regional aerosol/haze transport significantly reduces the boundary layer height to less than 1 km compared to haze-free (clear) days (∼ 2–2.5 km), mainly during the ensuing period of boundary layer evolution over the eastern coast. Consequently, an increase in PM2.5 concentration over Chennai is observed (∼ 50 %–60 %) during RTE compared to background days. This study provides robust observational evidence of the importance of regional transport of aerosols for the air quality of downwind megacities and warrants more observational and modeling studies in the future.